2023
DOI: 10.1021/jacs.3c03309
|View full text |Cite
|
Sign up to set email alerts
|

Scalable and Depurative Zirconium Metal–Organic Framework for Deep Flue-Gas Desulfurization and SO2 Recovery

Abstract: Deep SO 2 removal and recovery as industrial feedstock are of importance in flue-gas desulfurization and natural-gas purification, yet developing low-cost and scalable physisorbents with high efficiency and recyclability remains a challenge. Herein, we develop a viable synthetic protocol to produce DUT-67 with a controllable MOF structure, excellent crystallinity, adjustable shape/size, milli-to-kilogram scale, and consecutive production by recycling the solvent/modulator. Furthermore, simple HCl post-treatmen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
15
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 40 publications
(16 citation statements)
references
References 58 publications
1
15
0
Order By: Relevance
“…The value of 3.5 mmol g −1 can compete with those of the reported porous materials under the same conditions, such as BIDC-3-800 (4.57 mmol g −1 ), 6 TAM-POF (4.52 mmol g −1 ), 25 HNIP-TBMB-1 (3.39–3.54 mmol g −1 ), 39 ECUT-100 (3.3 mmol g −1 ), 14 ECUT-Th-60 (2.5 mmol g −1 ), 16 ELM-12 (1.95 mmol g −1 ), 12 sPAN-2 (1.9 mmol g −1 ), 26 HNIP-DCX-1 (1.57 mmol g −1 ), 39 and ECUT-77 (0.48 mmol g −1 ). 13 Surprisingly, ANOP-4 demonstrates a notable uptake of 21.9 mmol g −1 SO 2 at 273 K and 100 kPa (Table 2), surpassing the performance of several previously reported porous materials, such as TAM-POF (about 13.0 mmol g −1 ), 25 viologen-POF (about 18.3 mmol g −1 ), 24 DUTs (about 10.3–10.6 mmol g −1 ), 17 sPANs (8.45–9.36 mmol g −1 ), 26 and CTFs (4.4–6.7 mmol g −1 ). 22 Additionally, when the measurement temperature was increased from 273 K to 298 K, the SO 2 adsorption capacities of both ANOPs decreased slightly due to their physisorption characteristics.…”
Section: Resultsmentioning
confidence: 58%
See 1 more Smart Citation
“…The value of 3.5 mmol g −1 can compete with those of the reported porous materials under the same conditions, such as BIDC-3-800 (4.57 mmol g −1 ), 6 TAM-POF (4.52 mmol g −1 ), 25 HNIP-TBMB-1 (3.39–3.54 mmol g −1 ), 39 ECUT-100 (3.3 mmol g −1 ), 14 ECUT-Th-60 (2.5 mmol g −1 ), 16 ELM-12 (1.95 mmol g −1 ), 12 sPAN-2 (1.9 mmol g −1 ), 26 HNIP-DCX-1 (1.57 mmol g −1 ), 39 and ECUT-77 (0.48 mmol g −1 ). 13 Surprisingly, ANOP-4 demonstrates a notable uptake of 21.9 mmol g −1 SO 2 at 273 K and 100 kPa (Table 2), surpassing the performance of several previously reported porous materials, such as TAM-POF (about 13.0 mmol g −1 ), 25 viologen-POF (about 18.3 mmol g −1 ), 24 DUTs (about 10.3–10.6 mmol g −1 ), 17 sPANs (8.45–9.36 mmol g −1 ), 26 and CTFs (4.4–6.7 mmol g −1 ). 22 Additionally, when the measurement temperature was increased from 273 K to 298 K, the SO 2 adsorption capacities of both ANOPs decreased slightly due to their physisorption characteristics.…”
Section: Resultsmentioning
confidence: 58%
“…Compared to conventional absorption processes, physisorption is known to be a powerful strategy for the convenient and energy-efficient capture of SO 2 , and involves the use of various porous adsorbents, such as porous carbon, 6–11 metal–organic frameworks (MOFs), 12–21 and nanoporous organic polymers (NOPs), 22–27 which serve as major adsorbents for physisorption. Among these materials, NOPs have been regarded as promising candidates for SO 2 capture due to their wide range of reactions, high surface area, and excellent chemical and thermal stabilities.…”
Section: Introductionmentioning
confidence: 99%
“…The emission of sulfur dioxide (SO 2 ) from flue gas is harmful to the environment and human health, but SO 2 is also an important source for the industrial production of sulfuric acid if it is separated, purified, and recovered . Trace SO 2 deactivates amine-based scrubbers, causes pipeline corrosion during gas transportation, and irreversibly poisons catalysts for selective NO x reduction and CH 4 combustion. , Trace SO 2 needs to be removed at 0.002 bar with high selectivity in deep desulfurization. , Due to the designability and tunability of pore structures as well as high chemical stability, COFs are promising physical absorbents for the separation and recovery of SO 2 but remain to be explored. The isotherm for the adsorption of SO 2 with COF-AB-c was then investigated at 298 K. At 0.002 bar, COF-AB-c uptakes 22 cm 3 g –1 SO 2 , which is 2200 and 733% of that for COF-B (1.0 cm 3 g –1 ) and COF-A (3.0 cm 3 g –1 ), respectively (Figure a).…”
Section: Results and Discussionmentioning
confidence: 99%
“…However, low working capacity and dissatisfactory selectivity make them not the best choice for physical sorption separation . Metal–organic frameworks (MOFs) have shown great potential in gas adsorption and separation due to their high surface area, modified pores, adjusted topological structure, and high adsorption capacity, as compared to traditional porous materials like zeolites and activated carbon. Several classic MOFs, including ZU-801, DUT-52, ZJU, , and DMOF, have exhibited excellent gas storage and separation performance. Researchers have made efforts to enhance gas adsorption and separation properties by functionalizing MOFs through the introduction of functional groups (−CH 3 , −NH 2 , −OH), tuning of pore size and the construction of open metal sites (OMSs). Previous studies have shown that providing an appropriate aromatic pore environment can enhance interactions between light hydrocarbon molecules and the MOF framework through dispersion and induction forces, a widely used and effective approach. , Our research group is committing to the engineering of pores to achieve efficient gas capture. ,,, In our work, we aim to introduce additional functional sites into the aromatic pore environment to achieve a synergistic effect from multiple adsorption sites.…”
Section: Introductionmentioning
confidence: 99%